2019
DOI: 10.1002/chem.201900996
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Cyclisation by 1,4‐Dioxidation

Abstract: Amide-substituted diynes were cyclized in the presence of ac ationic gold catalyst and an external nucleophile leadingt o1 -indenones and 1-iminoindenones. The electron-donating features of the nitrogen atom enable the formation of ar eactive ketenei miniumi on, which can be trapped by either diphenyl sulfoxide or anthranil as nucleophiles in as ubsequent oxidations tep, providings ubstituted inden-1-on-3-carboxamides.Scheme1.Dual activationofd iynes andfurtherreactions.Scheme2.Formation of ak etene iminiumi o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 91 publications
(15 reference statements)
0
14
0
Order By: Relevance
“…Thus, elimination of pyridine motif allows the formation of gold carbene species In 2019, a cationic Au catalyzed cyclization of amidesubstituted diynes and an external nucleophile was reported by Hashmi and co-workers, leading to 1-indenones 80 and 1iminoindenones (Scheme 41). [45] The reaction involves an In the same year, the Cui and co-workers demonstrated an iterative assembly of nitrile oxides 81 and ynamides for the synthesis of isoxazoles 82 and pyrroles 83 (Scheme 42). [46] The nitrile oxides 81 a, generated in situ from 81, at first undergoes Cu(I)-free cyclization with terminal ynamides to yield isoxazoles 82.…”
Section: Combination Of O-based Nucleophiles and Gold Keteniminium Speciesmentioning
confidence: 99%
“…Thus, elimination of pyridine motif allows the formation of gold carbene species In 2019, a cationic Au catalyzed cyclization of amidesubstituted diynes and an external nucleophile was reported by Hashmi and co-workers, leading to 1-indenones 80 and 1iminoindenones (Scheme 41). [45] The reaction involves an In the same year, the Cui and co-workers demonstrated an iterative assembly of nitrile oxides 81 and ynamides for the synthesis of isoxazoles 82 and pyrroles 83 (Scheme 42). [46] The nitrile oxides 81 a, generated in situ from 81, at first undergoes Cu(I)-free cyclization with terminal ynamides to yield isoxazoles 82.…”
Section: Combination Of O-based Nucleophiles and Gold Keteniminium Speciesmentioning
confidence: 99%
“…Interestingly, it has also been evident that the expected carbene-oxidation product can also be obtained via a non-carbene transfer pathway. [26,27] As a result, various research groups have performed DFT calculations in addition to experimental studies to delineate the operating mechanism.…”
Section: Reactions Of Gold Carbene With Alkyne: the Mechanistic Premisementioning
confidence: 99%
“…Although it should be noted that, the failure in trapping the latent gold‐carbene species with such carbene trap experiments are only a negative indication for [1,n]‐carbene transfer process and do not substantiate any other pathway. Interestingly, it has also been evident that the expected carbene‐oxidation product can also be obtained via a non‐carbene transfer pathway [26,27] . As a result, various research groups have performed DFT calculations in addition to experimental studies to delineate the operating mechanism.…”
Section: Reactions Of Gold Carbene With Alkyne: the Mechanistic Premisementioning
confidence: 99%
“…[16e] Hashmi and coworkers developed synthesis of indenones from amide substituted diynes under cationic gold catalysis along with diphenyl sulfoxide [Scheme 1 (vii)]. [20] And it was reported that instead of diphenyl sulfoxide they have tested with N-oxide. However, the desired products was not achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Substituted indenones were synthesized by converting 1,2‐dialkynylbenzenes by utilizing I 2 O 5 and water [Scheme 1 (vi)] [16e] . Hashmi and co‐workers developed synthesis of indenones from amide substituted diynes under cationic gold catalysis along with diphenyl sulfoxide [Scheme 1 (vii)] [20] . And it was reported that instead of diphenyl sulfoxide they have tested with N ‐oxide.…”
Section: Introductionmentioning
confidence: 99%